THE ROLE OF COMMUNITIES LIVING IN WATERSHEDS TOWARDS FLOOD DISASTER MANAGEMENT : SYSTEMATIC REVIEW - Suroso, Heri; Enggar Fitri, Loeki; Sri Hayati, Yati (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Disaster is a series of events that can threaten and disrupt human life, caused by natural and non-natural factors. A flood disaster is a natural disaster that can occur due to extreme storms in the upper watersheds, climate change, and geomorphological conditions of soil slopes, erosion, and sediment material. Flood disasters will have an impact on the social situation, people's economy, health status and death. Method. A systematic review was conducted through several stages, namely making questions, identifying, eligibility, selecting article inclusions, screening, and appraisal. The selection process was listed in the Systematic review framework and 10 articles are obtained. Later, articles were summarized and rated according to The Joanna Briggs Institute (JBI) in each article. Result&Analysis. The data shows that the results vary according to the system, and the conditions in which the study was conducted. Increasing the role of the community in flood disaster management efforts is done by increasing community knowledge, skills and experience, related to an efficient disaster management system, with several methods, namely by giving questionnaires and conducting interviews with the community or family, special training and simulations. Discussion. To increase the awareness and role of the community in managing flood disasters, several methods are applied. The simulation method is an educational effort that can be used to improve people's knowledge, skills, and experience in conducting flood management activities.